Emotional Semantic in Indonesian: A Literature Study on Facial Expressions and Body Language - Andri Purwanugraha (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze the relationship between emotional semantics in the Indonesian language and the expression of emotions through facial expressions and body language as components of nonverbal communication within the Indonesian cultural context. Employing a descriptive qualitative approach and a literature review method, this research examines the concepts of emotional semantics, facial expression theories, body language, and multimodality based on linguistic, psychological, and communication studies. The findings indicate that emotional meaning in Indonesian is contextual, gradational, and strongly influenced by cultural norms that emphasize social harmony and politeness. Facial expressions and body language play a crucial role as nonverbal markers that clarify, reinforce, or even modify verbal meaning. These results demonstrate that the analysis of emotional semantics must account for the integration of verbal and nonverbal channels, highlighting the necessity of a multimodal approach to understanding emotional representation in Indonesian communication.